2013
DOI: 10.1155/2013/943636
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Resources and Tools for Conformational B-Cell Epitope Prediction

Abstract: Identification of epitopes which invoke strong humoral responses is an essential issue in the field of immunology. Localizing epitopes by experimental methods is expensive in terms of time, cost, and effort; therefore, computational methods feature for its low cost and high speed was employed to predict B-cell epitopes. In this paper, we review the recent advance of bioinformatics resources and tools in conformational B-cell epitope prediction, including databases, algorithms, web servers, and their applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 81 publications
1
90
0
1
Order By: Relevance
“…ABCpred is based on standard feed-forward (FNN) and recurrent neural network (RNN) for predicting B-cell epitopes in an antigenic sequence with an estimated accuracy of 65.9% [65].…”
Section: Mimotope-based Prediction Methodsmentioning
confidence: 99%
“…ABCpred is based on standard feed-forward (FNN) and recurrent neural network (RNN) for predicting B-cell epitopes in an antigenic sequence with an estimated accuracy of 65.9% [65].…”
Section: Mimotope-based Prediction Methodsmentioning
confidence: 99%
“…Continuous B cell epitope prediction is very similar to T cell epitope prediction, which has mainly been based on the amino acid properties such as hydrophilicity, charge, exposed surface area and secondary structure. Discontinuous B cell epitope prediction requires 3D structure of the antigen [54][55][56]. To date, some specific resources to predict continuous or discontinuous B-cell epitopes are available on the Web (Table 3).…”
Section: Bioinformatics Tools To Predic Potential T Cell Binding-epitmentioning
confidence: 99%
“…The prediction accuracy for models based on these properties varies from 52.92% to 57.53% [57]. The ABCpred server, which is based on neural networks, has an estimated accuracy of 65.93% [54]. Another server called BepiPred predicts the location of linear B-cell epitopes using a combination of a hidden Markov model and a propensity scale method [58].…”
Section: Bioinformatics Tools To Predic Potential T Cell Binding-epitmentioning
confidence: 99%
“…The accuracy of this computational approach has been greatly enhanced using statistical methods. 33 Many of researchers have used the VP8 and S2 antigens as a candidate vaccine in different expression schemes like baculovirus, 34 E.coli, 35,36 and concluded that these antigens can be considered an immunogen in vaccine studies against the BRV and BCV. 37,7 The main strategy in this study was to design a chimeric antigen (named VP8-S2) carrying various epitopes of the BRV and BCV for co-expression them into E.coli.…”
Section: Protein Expression and Purification Analysesmentioning
confidence: 99%